Bluephage: A rapid method for the detection of somatic coliphages used as indicators of fecal pollution in water. (1st January 2018) - Muniesa, M.; Ballesté, E.; Imamovic, L.; Pascual-Benito, M.; Toribio-Avedillo, D.; Lucena, F.; Blanch, A.R.; Jofre, J.
Abstract: The use of somatic coliphages as indicators of fecal and viral pollution in water and food has great potential due to the reliability, reproducibility, speed and cost effectiveness of methods for their detection. Indeed, several countries already use this approach in their water management policies. Although standardized protocols for somatic coliphage detection are available, user-friendly commercial kits would facilitate their routine implementation in laboratories. The new method presented here allows detection of up to 1 somatic coliphage in under 3.5 h, well within one working day. The method is based on a modified Escherichia coli strain with knocked-out uidB and uidC genes, which encode the transport of glucuronic acid inside cells, and overexpressing uidA, which encodes the enzyme β-glucuronidase. The enzyme accumulated in the bacterial cells only has contact with its substrate after cell lysis, such as that caused by phages, since the strain cannot internalize the substrate. When the enzyme is released into the medium, which contains a chromogen analogous to glucuronic acid, it produces a change of color from yellow to dark blue. This microbiological method for the determination of fecal pollution via the detection of culturable microorganisms can be applied to diverse sample types and volumes for qualitative (presence/absence) and quantitative analysis and is the fastest reported to date. Graphical abstract: Image Highlights: Bluephage is a fast and easy method for the detection of somatic coliphages. The method allows detection of up 1 somatic coliphages in under 3.5 h. It is applicable to water, food and sludge. It is adaptable to different volumes. Provide quantification by MPN approach.